Impact of diabetes mellitus on clinical presentation and treatment response of smear positive pulmonary tuberculosis patients - K. P., Abdul Hashim; Ayoob, Muhammed Anas (International Journal of Research in Medical Sciences, 2017)
Background: Diabetes mellitus (DM) is a known risk factor for tuberculosis (TB). The aim of this study was to evaluate the effect of DM on clinical presentation and treatment response of sputum positive pulmonary tuberculosis patients. Methods: The present retrospective study was carried out in department of Pulmonary Medicine, Sree Gokulam Medical College and Research Foundation, Trivandrum, between January 2014 to December 2016. Results: Out of 205 subjects enrolled for this study, 73 were diagnosed with DM and 132 patients had no history of DM and were having HbA1c less than 6.5%. Mean HbA1c in DM group at presentation was 10.5 and in patients without DM group was 5.6. Low BMI was more in DM patients. Clinical characteristics at presentation were similar in both the groups. Patients with DM presented after long duration of symptoms (>8 weeks duration) and also with more atypical symptoms. On radiological examination, lower zone involvement and cavity lesions were more in patients with DM which was statistically significant. Clinical picture at the end of 6 months showed improvement in both the groups but radiological improvement was more in patients without DM compared to the other group. Conclusions: Uncontrolled DM is associated with high prevalence of Tuberculosis. Atypical symptoms and atypical radiological findings are more common in DM patients which lead to delayed presentation. Strategies are needed to ensure that optimal care is provided to patients with both diseases.